Dicraeosaurid Sauropod remains from the Mulichinco Formation (Valanginian, Lower Cretaceous), Neuquén Basin, Argentina - Windholz, Guillermo José (2017)
Fil: Windholz, Guilermo. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.